2008
DOI: 10.1371/journal.ppat.0040026
|View full text |Cite
|
Sign up to set email alerts
|

NetB, a New Toxin That Is Associated with Avian Necrotic Enteritis Caused by Clostridium perfringens

Abstract: For over 30 years a phospholipase C enzyme called alpha-toxin was thought to be the key virulence factor in necrotic enteritis caused by Clostridium perfringens. However, using a gene knockout mutant we have recently shown that alpha-toxin is not essential for pathogenesis. We have now discovered a key virulence determinant. A novel toxin (NetB) was identified in a C. perfringens strain isolated from a chicken suffering from necrotic enteritis (NE). The toxin displayed limited amino acid sequence similarity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
551
6
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 525 publications
(593 citation statements)
references
References 46 publications
22
551
6
14
Order By: Relevance
“…Based on recent reports describing the association of netb and NE, the detection of this gene might also be interesting for a complete laboratory diagnosis (KEYBURN et al, 2008). Intestinal damage and increases in liver condemnation during slaughterhouse inspections strongly suggest NE.…”
Section: Broiler Chickensmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on recent reports describing the association of netb and NE, the detection of this gene might also be interesting for a complete laboratory diagnosis (KEYBURN et al, 2008). Intestinal damage and increases in liver condemnation during slaughterhouse inspections strongly suggest NE.…”
Section: Broiler Chickensmentioning
confidence: 98%
“…One of the most interesting of these is Necrotic Enteritis toxin B (NetB), a poreforming toxin capable of causing lesions typical of NE in experimental models (KEYBURN et al, 2008). In addition, it was demonstrated that the NetB-encoding gene (netb) is common in C. perfringens type A isolates from NE birds, whereas it is rare in healthy birds (KEYBURN et al, 2008).…”
Section: Broiler Chickensmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades after the definitive description of necrotic enteritis by Parish 11 it was thought that alpha-toxin, a toxin produced by all isolates of C. perfringens, was the main virulence determinant. However, in 2006, we demonstrated that alpha-toxin was not essential for experimental disease induction 12 and then went on to discover and characterise the toxin, necrotic enteritis toxin B-like (NetB), that does play an essential role in virulence 13,14 .…”
mentioning
confidence: 99%
“…The anaerobe bacteriology were performed (SILVA et al, 2013) and characteristic C. perfringens colonies were subjected to multiplex (VIEIRA et al, 2008) and netB (necrotic enteritis B-like toxin) PCR (KEYBURN et al, 2008).…”
mentioning
confidence: 99%